Tumor heterogeneity and clonal cooperation influence the immune selection of IFN-γ-signaling mutant cancer cells - Jason B. Williams (Nature Portfolio, 2020)
Melanoma is a cancer that responds relatively well to immunotherapy but resistance does ensue. Here, the authors show that loss of IFNGR2 or JAK1 in a melanoma cell line enhances T cell mediated lysis, however these cells are paradoxically more sensitive to immune-mediated tumor control in vivo due to the loss of PD-L1.